Socioeconomically disadvantaged smokers' ratings of plain and branded cigarette packaging: an experimental study. Issue 2 (6th February 2014) - Guillaumier, Ashleigh; Bonevski, Billie; Paul, Chris; Durkin, Sarah; D'Este, Catherine
Abstract : Objectives: This study aimed to test the potential impact of plain packaging for cigarettes on brand appeal among highly socioeconomically disadvantaged smokers using the new design for cigarettes implemented in Australia, which combines plain packaging with larger health warning labels. Design: A 2×2 factorial design trial embedded within a cross-sectional computer touchscreen survey. Data were collected between March and December 2012. Setting: Socially disadvantaged welfare aid recipients were recruited through a large Social and Community Service Organisation in New South Wales, Australia. Participants: N=354 smokers. The majority of the sample had not completed high school (64%), earned less than A300/week (55%) and received their income from Government payments (95%). Interventions: Participants were randomised to one of the four different pack conditions determined by brand name: Winfield versus Benson & Hedges, and packaging type: branded versus plain. Participants were required to rate their assigned pack on measures of brand appeal and purchase intentions. Results: Plain packaging was associated with significantly reduced smoker ratings of 'positive pack characteristics' (p<0.001), 'positive smoker characteristics' (p=0.003) and 'positive taste characteristics' (p=0.033) in the Winfield brand name condition only. Across the four pack conditions, no main differences were found for 'negative smoker characteristics' (p=0.427) or 'negative harm characteristics' (p=0.411). In comparison to plain packaging, the presentation of branded packaging was associated with higher odds of smokers' purchase intentions (OR=2.18, 95% CI 1.34 to 3.54; p=0.002). Conclusions: Plain packs stripped of branding elements, featuring larger health warning labels, were associated with reduced positive cigarette brand image and purchase intentions among highly socioeconomically disadvantaged smokers.